Improving nutrition through biofortification - Bouis, Howarth E.; Saltzman, Amy; Birol, Ekin (International Food Policy Research Institute, 2019)
There is much unfinished business in scaling up and mainstreaming biofortification. In 2018, HarvestPlus entered its fourth 5-year phase and is implementing its new strategic plan, which is designed to lay the groundwork for biofortification to benefit 1 billion consumers globally by 2030. In this new phase, HarvestPlus has commissioned efficacy studies on zinc biofortified crops, as well as effectiveness studies on both zinc and iron biofortified crops. Additional studies are planned to understand the efficacy of biofortification for additional target groups, like adolescents, and on health outcomes beyond micronutrient deficiency status. As part of this new phase, HarvestPlus will work closely with others to further elucidate the comparative advantages of different interventions (biofortification, fortification, and supplementation) across time and location and to establish optimal micronutrient intervention portfolios for scenarios such as global population growth and climate change. This new phase will also analyze, document and make publicly available the data, tools, processes, and the lessons learned from interventions to introduce and scale up biofortification. The ultimate aim of these efforts is to anchor biofortification within the various national and international policies, programs and investments in the agriculture and nutrition nexus.